2020
DOI: 10.1061/(asce)ee.1943-7870.0001686
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Cybersecurity Incidents in the Water Sector

Abstract: This study presents a critical review of disclosed, documented, and malicious cybersecurity incidents in the water sector to inform safeguarding efforts against cybersecurity threats. The review is presented within a technical context of industrial control system architectures, attack-defense models, and security solutions. Fifteen incidents have been selected and analyzed through a search 1 Hassanzadeh strategy that included a variety of public information sources ranging from federal investigation reports to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(81 citation statements)
references
References 17 publications
0
78
0
3
Order By: Relevance
“…Water utilities face unprecedented pressures and complexity in their decision-making as a result population growth and challenges related to climate change such as heavy rainfall and drought periods. Further, an increasingly automated and interconnected world creates new sources of vulnerability, such as cyber-attacks to their automated system management [104,105] or the increasing likelihood of failure propagation through multiple, urban infrastructures [106]. However, digitalisation and interconnectivity also bring solutions to the challenges faced by a water utility today.…”
Section: Emergent Paradigm Of Digital Water and Future Research Direcmentioning
confidence: 99%
“…Water utilities face unprecedented pressures and complexity in their decision-making as a result population growth and challenges related to climate change such as heavy rainfall and drought periods. Further, an increasingly automated and interconnected world creates new sources of vulnerability, such as cyber-attacks to their automated system management [104,105] or the increasing likelihood of failure propagation through multiple, urban infrastructures [106]. However, digitalisation and interconnectivity also bring solutions to the challenges faced by a water utility today.…”
Section: Emergent Paradigm Of Digital Water and Future Research Direcmentioning
confidence: 99%
“…A recent study presented a review of fifteen cybersecurity incidents in the water and wastewater sector covering a wide variety of vulnerabilities and situations from the Maroochy Shire Sewage Treatment Plant insider attack in 2001 to the Riviera Beach Water Utility ransomware attack in 2019 [9]. The study found that the sheer diversity of the systems, attackers, and consequences associated with the incidents indicate a need for inclusive and comprehensive vulnerability assessments, as well as risk mitigation, preparedness, response, and recovery studies that account for such extreme heterogeneity.…”
Section: Emerging Cyber Security Needs In the Water Industrymentioning
confidence: 99%
“…For instance, the Iranian Revolutionary Guard are said to have attacked the Bowman Avenue Dam in New York state, gaining control of the command and control system, with the ability to produce kinetic effects on the water system. While the flood gates were offline for maintenance and were therefore not accessible within the attack, this was fortuitous and demonstrates how vulnerable systems may actually be [23]. The 2016 attack on the "Kemuri" water plant (a pseudonym given to the plant), attributed to political hackers affiliated to Syria, gained control the levels of chemicals used within the water system, as well as retrieving large quantities of personal customer data [24].…”
Section: Cyber-attacks On Water Networkmentioning
confidence: 99%
“…In yet another, in 2019, governmental services, including water, in Florida were targeted in a ransomware attack. The attack compromised Riviera Beach Water Utility's computer systems, preventing them from using their pumping stations, water quality testing functions and their payment operations [23].…”
Section: Cyber-attacks On Water Networkmentioning
confidence: 99%